Implementasi Profil Pelajar Pancasila Karakter Beriman dan Bertakwa Kepada Tuhan YME dan Berakhlak Mulia Untuk Calon Guru SD - Muhammad Arifin Arif; Yasyir Fahmi Mubaraq (Schemata: Jurnal Pascasarjana UIN Mataram, 2025)
This study aims to describe how the Pancasila student profile is implemented for prospective elementary school teachers. This is a descriptive qualitative study, with 10 prospective teachers or students majoring in Elementary School Teacher Education at PGRI University Kalimantan as the research subjects. Data collection techniques include questionnaires, interviews, and documentation. Data analysis techniques involve data grouping and data synthesis. The research findings indicate that: (1) The implementation of the Pancasila student profile for prospective elementary school teachers, specifically the character traits of being faithful and devout to God Almighty and having noble moral values, involves understanding religious ethics through the 20 obligatory and impossible attributes of Allah SWT. Among the 5 sample participants, the following results were obtained: a) 5 participants were highly proficient in identifying the 20 obligatory and impossible attributes of Allah SWT. b) 1 person was highly proficient, 2 were proficient, and 2 were less proficient in memorizing the 20 obligatory and impossible attributes of Allah SWT. c) 1 person was highly proficient, 1 was proficient, and 3 were less proficient in distinguishing the 20 obligatory and impossible attributes of Allah SWT. Thus, it can be concluded that the implementation of the Pancasila Student Profile through intraschool activities and projects has an impact on the proficiency of faith and piety toward God Almighty, as well as noble character among prospective elementary school teachers. The implication is that graduates with such character are expected to become role models for students, create a learning environment based on moral values, and contribute to building a generation with integrity and personality in line with the values of Pancasila. Keywords: Prospective Elementary School Teachers, Implementation, Pancasila Profile Penelitian ini bertujuan untuk mendiskripsikan mengenai bagaimana implementasi profil pelajar pancasila untuk calon guru SD. Jenis penelitian ini adalah penelitian kualitatif deskriptif, subjek penelitian adalah 10 orangcalon guru atau mahasiswa prodi Pendidikan Guru Sekolah Dasar di Universitas PGRI Kalimantan. Teknik pengumpulan data dilakukan melalui angket atau kuesioner, wawancara dan dokumentasi.Teknik analisis data dilakukan dengan pengelompokan data, dan menyimpulkan data. Hasil penelitian menunjukan bahwa: (1)Implementasi profil pelajar pancasila karakter beriman dan bertakwa kepada Tuhan YME dan berakhlak mulia untuk calon guru SD, ialah pemahaman terhadap akhlak beragama melalui 20 sifat wajib dan mustahil bagi Allah SWT melalui 5 orang sample di dapatkan: a) 5 orang sangat mahir dalam menyebutkan 20 sifat wajib dan mustahil bagi Allah SWT b) 1 orang sangat mahir, 2 orang mahir, dan 2 orang kurang mahir dalam menghafal 20 sifat wajib dan mustahil bagi Allah SWT. c)1 orang sangat mahir, 1 orang mahir, 3 orang kurang mahir dalam membedakan 20 sifat wajib dan mustahil bagi Allah SWT.. Dengan demikian, dapat disimpulkan bahwa implementasi Profil Pelajar Pancasila melalui kegiatan intrakurikuler dan projek memberikan dampak kemahiran pada karakter beriman dan bertakwa kepada Tuhan YME serta berakhlak mulia pada mahasiswa calon guru SD. Implikasinya, lulusan yang memiliki karakter tersebut diharapkan mampu menjadi teladan bagi peserta didik, menciptakan lingkungan belajar yang berbasis nilai-nilai moral, serta berkontribusi dalam membangun generasi yang berintegritas dan berkepribadian sesuai dengan nilai-nilai Pancasila. Kata kunci: Calon Guru SD, Implementasi, Profil Pancasila